Improved survival with second-line hepatic arterial infusion chemotherapy after atezolizumab-bevacizumab failure in hepatocellular carcinoma - Lee, Ji Yeon; Lee, Jaejun; Kim, Suho; Yoo, Jae-sung; Kim, Ji Hoon; Yang, Keungmo; Han, Ji Won; Jang, Jeong Won; Choi, Jong Yong; Yoon, Seung Kew; Chun, Ho Jong; Oh, Jung Suk; et al. (Frontiers in Oncology, 2024)
BackgroundThere is no established second-line treatment for hepatocellular carcinoma (HCC) following atezolizumab-bevacizumab (ate-beva) failure. This study assessed the efficacy of hepatic arterial infusion chemotherapy (HAIC) as a salvage therapy by comparing survival outcomes and treatment responses between HAIC as a first-line treatment and as a second-line option after ate-beva failure.Materials and MethodsWe retrospectively analyzed 100 patients with advanced HCC treated with HAIC between March 2022 and July 2024. Patients were categorized into two groups: those who received HAIC as initial therapy (first-line HAIC group) and those who received HAIC following ate-beva failure (post-ate-beva group). Survival outcomes were assessed with Kaplan-Meier curves and log-rank tests, and factors associated with survival were identified through Cox regression analysis.ResultsThe post-ate-beva group exhibited longer overall survival (OS) (median OS 12.4 months) compared to the first-line HAIC group (median OS 6.8 months) (p = 0.073). Progression-free survival (PFS) was significantly superior in the post-ate-beva group (median PFS 8.2 months) compared to the first-line HAIC group (median PFS 3.1 months) (p = 0.018). The objective response rate was also notably higher in the post-ate-beva group than in the first-line HAIC group (35.3% vs. 18.1%, p = 0.031). In multivariate analysis, HAIC following ate-beva failure, compared to first-line HAIC, was significantly associated with favorable outcomes for both OS (p = 0.014) and PFS (p = 0.006).ConclusionThe superior survival outcomes and treatment responses observed in the post-ate-beva group suggest that HAIC may be an effective second-line treatment option for advanced HCC following ate-beva therapy failure. However, due to the retrospective nature and small sample size of the study, further prospective studies with larger patient populations are needed to strengthen the evidence.